Use of soybean meal-based moxifloxacin pellets in equine nutrition and health - Velazquez, Desiderio Rodriguez; Guerrero, Jorge Antonio Varela; Alvarado, Tonantzin Díaz; Orozco, Diego Girón; Salem, Abdelfattah Zeidan Mohamed; Kreuzer-Redmer, Susanne; Elghandour, Mona Mohamed Yasseen (Frontiers in Animal Science, 2025)
Pellets formulated from organic biomass, such as soybean meal, are increasingly used in animal nutrition and controlled drug delivery systems. This review aims to explore the advancements and challenges in developing and evaluating soybean meal-based moxifloxacin pellets specifically for equine applications. The focus includes production techniques, the role of soybean meal in equine diets, and the therapeutic potential of moxifloxacin. Soybean meal, known for its high protein and lysine content, is a valuable feed component for equines and offers advantages in pellet formulation. Moxifloxacin, a broad-spectrum antibiotic, has shown effectiveness in treating a range of bacterial infections in horses, with the added benefit of controlled release when delivered in pellet form. This combination presents a novel strategy for improving both nutrition and targeted medication in equines. However, further research is required to assess its safety and therapeutic efficacy.